Aplicação do modelo computacional para magneto-acreção e ventosmagneto-centrífugos no cálculo de perfis de H de estrelas T Tauri Clássicas - Tatiana Moura Costa (2014)
Classical T Tauri stars are young (< 106 yr), low mass (< 2M ) stars that present strong spectral lines in emission. These lines originate mainly in the stellar magnetosphere, due to the accretion of gas from a circumstellar disk. The star-disk interaction is mediated by the intense stellar magnetic field that truncates the disk. Magnetic field lines drive gas from the disk to the star, forming accretion columns, which are heated to temperatures where the H emission probability is significant. Magnetic field lines also take away material from the disk, through magneto-centrifugally driven winds. The goal of this dissertation was to model H emission line profiles of young star-disk systems with well known physical parameters. We used the Lima et al. (2010) model that includes a dipolar and axisymmetric stellar magnetosphere radiatively coupled to a disk wind. We successfully reproduced the H line profiles of the classical T Tauri stars AA Tau and TW Hya, validating the theoretical emission line model.